MANDALA DALAM KESASTRAAN LAMA SEBUAH REFLEKSI KREASI TRADISI - Purnomo, S. Bambang (Balai Bahasa Jawa Timur, 2008)
Several cultural-religions (i.e. Hindu, Buddha, and than Islam) have influenced the Nusantara's writing traditions for along time. It can be realized in any literary-work that have appeared in this archipelago. There is the Mandala-literary aspect that it existence through has had influence to the manuscript traditions for along time ago. In Javanese-culture, those aspects are so influential in the oral-traditions and any architecture-arts To understand the quality and potential of cultural values available in the texts of Old Javanese Literary work that serve invaluable contributions to the history on nation's culture and humanity, the following study is meant to find out a representative literary text to be analyzed so that it is possible to reveal its philosopical and didactic values. The findings of study, using several approaches mentioned above, are a set of cultural values that have some close relationships with the system of poetica, the system of morality, or character building. This aspect can be classified as philosopical-didactic aspect of the classical Javanese literary text that is hypothetically useful for human being's life and living.